Analisis Faktor Kinerja Guru dalam Aspek Kepemimpinan dan Komunikasi Kepala Sekolah serta Keterkaitannya dengan Motivasi Kerja Guru - Juwaeni, Hamdan (Universitas Muhammadiyah Surakarta, 2014)
This research aims to examine (1) the contribution level of leadership and communication of school principal on the teachersâ performance through their motivation, (2) the contribution level of principalâs leadership and communication on teachersâÂ work motivation, and (3) the contribution level of teachersâ work motivation on their performance. This research uses quantitative approach. Population used in this research was taken from elementary school teachers in UPT Dinas Dikpora, Jebres District, Surakarta: from the total number 762 teachers, 262 teachers were selected as the samples. The data were collected by using questionnaire. Path data analysis technique used in this research. These are the research results.(1)There is no any contribution of school principalâs leadership and communication on the teachersâ performance through their motivation, with result criteria< x = 0,035 <(0,405 x 0,238) = 0,035 < 0,096,Â There is indirect Relationship pattern and > x = 0,161>(0,405 x 0,202) = 0,161 > 0,082, there is direct relationship pattern. (2) There is a positive contribution of the school principalâs leadership and communication on teachersâ work motivation; the result of >, is 23,756 > 2,639 with significant value < 0,05; 0,000. (3) There is a positive contribution of teachersâ workÂ motivation on their performance; the t-test analysis shows that 6,922 is >1,989 with p value (significance) <0,05, yaitu 0,000.